Activation of ERα signaling differentially modulates IFN-γ induced HLA-class II expression in breast cancer cells. - Ahmed A Mostafa; Dianne Codner; Kensuke Hirasawa; Yumiko Komatsu; Matthew N Young; Viktor Steimle; Sheila Drover (PLoS ONE, 2014)
The coordinate regulation of HLA class II (HLA-II) is controlled by the class II transactivator, CIITA, and is crucial for the development of anti-tumor immunity. HLA-II in breast carcinoma is associated with increased IFN-γ levels, reduced expression of the estrogen receptor (ER) and reduced age at diagnosis. Here, we tested the hypothesis that estradiol (E₂) and ERα signaling contribute to the regulation of IFN-γ inducible HLA-II in breast cancer cells. Using a panel of established ER⁻ and ER⁺ breast cancer cell lines, we showed that E₂ attenuated HLA-DR in two ER⁺ lines (MCF-7 and BT-474), but not in T47D, while it augmented expression in ER⁻ lines, SK-BR-3 and MDA-MB-231. To further study the mechanism(s), we used paired transfectants: ERα⁺ MC2 (MDA-MB-231 c10A transfected with the wild type ERα gene) and ERα⁻ VC5 (MDA-MB-231 c10A transfected with the empty vector), treated or not with E₂ and IFN-γ. HLA-II and CIITA were severely reduced in MC2 compared to VC5 and were further exacerbated by E₂ treatment. Reduced expression occurred at the level of the IFN-γ inducible CIITA promoter IV. The anti-estrogen ICI 182,780 and gene silencing with ESR1 siRNA reversed the E2 inhibitory effects, signifying an antagonistic role for activated ERα on CIITA pIV activity. Moreover, STAT1 signaling, necessary for CIITA pIV activation, and selected STAT1 regulated genes were variably downregulated by E₂ in transfected and endogenous ERα positive breast cancer cells, whereas STAT1 signaling was noticeably augmented in ERα⁻ breast cancer cells. Collectively, these results imply immune escape mechanisms in ERα⁺ breast cancer may be facilitated through an ERα suppressive mechanism on IFN-γ signaling.